DEVELOPING EFFECTIVE ESP LEARNING MATERIALS USING A LEARNING MANAGEMENT SYSTEM IN TERTIARY EDUCATION - Manan, Nanan Abdul; Badroeni, Badroeni (English Review: Journal of English Education, 2025)
This study aimed to conduct a needs analysis for developing an English for Specific Purposes (ESP) teaching model at Muhammadiyah Kuningan College of Teacher Training and Education in West Java, Indonesia. The research involved 104 students enrolled in the Information and Communication Technology Education program, aged between 19 and 21 years. Additionally, six lecturers, holding master’s degrees in Information Technology and possessing teaching experience ranging from three to ten years, participated in the study. Data from students were gathered through a multiple-choice questionnaire administered via the Ruangmu Learning Management System (LMS), focusing on three key areas: prerequisites, challenges, and educational aspirations. The feasibility of the LMS-based ESP model was also assessed using a validated instrument endorsed by experts. Results highlighted the importance of a detailed needs analysis in identifying knowledge gaps, forming the basis for developing an effective teaching model. A gap analysis helped bridge the disparity between current and required competencies. Pre-test scores revealed averages of 59.32, with the median, lowest, and highest scores being 60, 30, and 80, respectively. A clear improvement was observed in post-test results, indicating that the Ruangmu LMS had a positive impact on students' learning outcomes. The paired sample test further validated this enhancement, showing a statistically significant improvement with a two-tailed significance value of 0.00. In conclusion, the findings suggest that the Ruangmu LMS plays a critical role in improving student outcomes in English for Specific Purposes (ESP).